SURG-12. PAEDIATRIC BRAIN TUMOUR SURGERY: HOW CAN WE REPORT OUR SURGICAL OUTCOMES AND OPERATIVE MORBIDITY?. (4th December 2020) - Foster, Mitchell; Hennigan, Dawn; Greystone, Rebecca; van Baarsen, Kirsten; Sunderland, Geraint; Millward, Christopher; Srinivasan, Harishchandra; Ferguson, Deborah; Totimeh, Teddy; Pizer, Barry; Mallucci, Conor
Abstract: OBJECTIVE: Our objective was to quantify resection outcomes and operative morbidity in paediatric brain tumour surgery using existing scales, assessing their applicability. METHODS: We investigated morbidity using the Clavien-Dindo (CD) scale and the Drake classification. All paediatric patients receiving a biopsy or craniotomy for an intracranial tumour in a single tertiary paediatric neurosurgery centre between January 2008 and December 2018 were studied. Complications up to day 30 post op were graded. RESULTS: There were 459 operations: 92 biopsies and 367 craniotomies comprising 166 infratentorial and 292 supratentorial tumours. Median age was 9 years (56% male). The surgical goal was achieved or exceeded in 94% of cases. Thirty-day mortality was 1.31% with all deaths related to disease and none to surgical complications. The overall CD score was 1 in 10.9% of cases, 2 in 18.9%, 3A in 1.7%, 3B in 11.8%, and 4 in 1.1%. There was no operative morbidity in 54% of cases. Using the Drake classification, meningitis was seen in 3.92% of cases, seizures in 3.92%, neurological deficit (that persisted at 30 days) in 8.5%, CSF leak in 5.01%, wound infection in 1.96%, haemorrhage 1.75 %, shunt infection in 1.53%, shunt block in 0.65%, medical complications in 2.4%, and others in 3.05%. CONCLUSIONS: This is the largest series presenting morbidity from paediatric brain tumour surgery, and the first to validate the CD scale. Our morbidity on the Drake scale was comparable with other series. There is a need to develop improved tools to quantify morbidity in this high-risk specialty.